Genetic variation in biochemical traits in seeds of two natural populations of Genipa americana L.: 1-individual and univariate analyses - Oliveira, Simone Aparecida de [UNESP]; Bonjorno, Ivan Iuri; Alves, Patricia Ferreira [UNESP]; Moraes, Marcela Aparecida de [UNESP]; Menezes Freitas, Miguel Luiz; Teixeira de Moraes, Mario Luiz [UNESP]; Teixeira de Moraes Polizeli, Maria de Lourdes (Ipef-inst Pesquisas Estudos Florestais, 2009)
Brazil is one of the world's richest countries in forest biodiversity. This has a great importance for humanity for sheltering essential scientific potential for the improvement in the quality of living beings. It also contributes to the preservation of natural resources and the environment. Among Brazil's forest species, jenipapo (Genipa americana L.) is commonly found in riparian vegetation. The objective of this work was to quantify the genetic variability of biochemical traits of seeds, as a support for in situ and ex situ conservation of natural populations of G. americana L. Two populations of the species were studied: one from Ilha Solteira, SP region (ISA) and other from Mogi Guacu, SP (MOG). In the ISA population, seeds were collected from 30 trees, and in the MOG population, from 22 trees. These seeds were analyzed for chemical composition: content of proteins, carbohydrates, lipids and starch. The two populations of G. americana studied had a great genetic variation for these traits. The population ISA had an additive and phenotypic correlation, which was negative and high for starch with lipid; and positive and medium, for lipid with prolamine, as well as for globulin with prolamine. The population MOG presented additive and phenotypic correlations: positive and medium for gluteline with globulin. In these populations, narrow sense heritability estimates of progenies were moderate (0.69 for carbohydrates in the population ISA) to high (0.81 to 0.99 for the other traits in the two populations), indicating that much progress can be expected with selection strategies.
Keywords: Chemical composition; Genetic parameters; Jenipapo; Progeny test; Seeds